A density functional theory study on the mechanism of simultaneous trifluoromethylation and oximation of aryl-substituted ethylenes. Issue 3 (June 2022) - Wang, Sen; Song, Wenlu; Lan, Xiaowei; Meng, Xuan; Li, Nan; Wei, Xianfu; Jing, Wenjie; Lu, Kui; Dai, Yujie
The effects of different substituents, located at the para position of the aromatic ring and at the β-carbon atom of styrenes, on difunctionalizations involving trifluoromethylation and oxime formation are investigated, showing that the difunctionalization reaction has a good adaptability to such reactants containing a range of substituents. This is important in the actual production process. It was found that proton transfer in the final tautomerism step involving transformation of a nitroso intermediate into an oxime is the rate-limiting step. The solvent effect did not influence the rate-limiting step significantly. Compared with direct proton transfer in a vacuum, the energy barrier of the final tautomerism step decreased from 57.80 kcal mol −1 in vacuum to 12.98 kcal mol −1 in water occurring via mediated proton transfer, which declines by 77.5%. When water participates in the rate-limiting steps in organic solvents, the energy barrier also decreases significantly, which indicates that a small amount of water in the organic solvent is conducive to the reaction.